Complaint behavior of Generation Z in tourism - Ksenija Leković; Dunja Kostić; Jelena Jevtić; Sanja Džever; Irena Petrušić (Anali Ekonomskog fakulteta u Subotici, 2025)
It can be observed that tourists behave differently when they have a negative experience. It is necessary to analyze the way in which the negative experience manifests itself when it comes to Generation Z. Considering that they are the creators of the online world, Generation Z manifests their dissatisfaction through public actions, private actions or they decide to behave without action. The aim of the research is to determine the connection between the ways Generation Z is expressing dissatisfaction in the tourism and the absence of a sense of shame when submitting complaints. The subject of research is the behavior of generation Z in tourism, with a focus on complaints. The empirical research was conducted with a focus on generation Z in the territory of the Republic of Serbia and contains 231 responses. To analyze and process the collected data, IBM SPSS Statistics software was used. The Pearson correlation test was used to analyze the correlation between the observed variables, after which hypotheses 2, 3 and 4 have been confirmed, and hypothesis 1 has been rejected.